The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1097/mpg.0b013e318213f9f6
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology, Diagnosis, and Management of Pediatric Ascites

Abstract: The pediatric population has a number of unique considerations related to the diagnosis and treatment of ascites. This review summarizes the physiologic mechanisms for cirrhotic and noncirrhotic ascites and provides a comprehensive list of reported etiologies stratified by the patient's age. Characteristic findings on physical examination, diagnostic imaging, and abdominal paracentesis are also reviewed, with particular attention to those aspects that are unique to children. Medical and surgical treatments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 160 publications
0
78
0
11
Order By: Relevance
“…5,8,31 Albumin infusion is also recommended for pediatric patients with a blood albumin level ≤ 2.5 g/dL to promote extravascular water reabsorption, associated with loop diuretics to produce more diuresis. 2,87 It has been observed that albumin infusion and water restriction correct HH in children, and other authors have proposed this treatment for adults, 88 but there are no good-quality studies to support this recommendation. 8,89 Albumin infusion alone or together with vasopressors may also be useful for the management of HH.…”
Section: Therapeutic Options Albumin Prescriptionmentioning
confidence: 99%
“…5,8,31 Albumin infusion is also recommended for pediatric patients with a blood albumin level ≤ 2.5 g/dL to promote extravascular water reabsorption, associated with loop diuretics to produce more diuresis. 2,87 It has been observed that albumin infusion and water restriction correct HH in children, and other authors have proposed this treatment for adults, 88 but there are no good-quality studies to support this recommendation. 8,89 Albumin infusion alone or together with vasopressors may also be useful for the management of HH.…”
Section: Therapeutic Options Albumin Prescriptionmentioning
confidence: 99%
“…2,3,5,6,[8][9][10][11][12][13] Además, consideraciones propias de esta edad dificultan a los pediatras basarse en recomendaciones extrapoladas de la población adulta.…”
Section: Introducción L a A S C I T I S S E D E F I N E C O M O L A Aunclassified
“…INTRODUCCIÓN L a a s c i t i s s e d e f i n e c o m o l a acumulación patológica de líquido en la cavidad peritoneal. [1][2][3] Es la complicación más frecuente de la cirrosis; su presencia marca un hito en la progresión de la enfermedad y está asociada a mala evolución. 4,5 El trasplante hepático es la opción terapéutica curativa para pacientes cirróticos con ascitis.…”
Section: Introductionunclassified
See 2 more Smart Citations